The Role of FOMO and Parasocial Interaction Through E-WOM on the Decision to Visit Bali’s Marine Tourism (Pusat Riset dan Inovasi Nasional, 2025)
Tourism has become one of Indonesia’s most dynamic sectors, with Bali positioned as a leading destination for marine-based attractions such as Amed, Tanjung Benoa, Menjangan, and Lovina. The rapid growth of social media platforms has transformed destination marketing, where psychological and digital factors increasingly shape tourist behavior. This study investigates the role of Fear of Missing Out (FOMO) and parasocial interaction in influencing domestic tourists’ decisions to visit Bali’s marine tourism, with electronic word-of-mouth (E-WOM) examined as a mediating variable. Using the Theory of Planned Behavior (TPB) as a framework, FOMO is conceptualized as shaping attitudes, parasocial interaction as influencing subjective norms, and E-WOM as enhancing perceived behavioral control. The research employed a quantitative approach with purposive sampling of 180 respondents who had engaged in marine tourism and actively used social media. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Results indicate that FOMO, parasocial interaction, and E-WOM each have significant positive effects on visit decisions. FOMO and parasocial interaction also significantly drive E-WOM activity, which partially mediates their influence on visiting decisions. The findings highlight that while psychological drivers and digital communication play a substantial role, external factors such as destination conditions, costs, and family preferences remain influential. This study contributes to tourism literature by clarifying inconsistent findings in prior research and emphasizing the importance of integrating psychological constructs with digital communication strategies. Practically, the results suggest that tourism stakeholders should optimize social media storytelling and encourage authentic E-WOM to strengthen destination appeal.